2000 tips for lecturers - Race, Philip (Kogan page, 1999)
This book brings together expert tips and guidance for all those lecturing and teaching in higher education. With ideas on all elements of their work, it covers issues facing lecturers and is intended for both experienced and inexperienced teachers.